A green and efficient photo-driven route for the selective oxidation of aqueous isopropanol solution to pinacol (C6) with hydrogen peroxide. (13th March 2017) - Li, Na; Yan, Wenjun; Zhang, Hongxia; Jia, Suping; Wang, Zhijian; Zheng, Jianfeng; Zhu, Zhenping
Abstract : The proposed strategy provides a green solution for the synthesis of aliphatic pinacol and offers a new design for the construction of C–C bonds with alphatic alcohol. Abstract : Selective oxidation of alcohols to highly valued chemicals in a clean manner ( e.g., with water as a solvent and O2 or H2 O2 as the primary oxidant) is the subject of considerable research attention. This paper presents a simple and environmentally friendly approach for the selective oxidation of isopropanol to pinacol C6 (2, 3-dimethyl-2, 3-butanediol) in water with hydrogen peroxide (H2 O2 ) through UV irradiation under mild conditions. A selectivity of 82–95% is achieved at H2 O2 feeding rates below 4 mL h −1 . The introduction of TiO2 nanotubes can further accelerate isopropanol conversion and enhance pinacol C6 formation. The highest formation rate of pinacol C6 and the highest conversion rate of isopropanol are 29.4 and 71.4 mmol h −1, respectively. The proposed strategy provides a green solution for the synthesis of aliphatic pinacol and offers a new design for the construction of C–C bonds with alphatic alcohol.